Synchronizing estrus in heifers with prostaglandin and Syncro-mate B - G. Jr. Heersche; G. Kiracofe; M. McKee; Duane L. Davis; G.R. Brower (Kansas Agricultural Experiment Station Research Reports, 1974)
Forty-seven of 50 heifers were in estrus 1 to 5 days after an injection of prostaglandin given when an ear implant of Synchro-mate B was removed. The implant had been in place one week. Thirty of the 47 (63.8%) heifers with synchronized estrus conceived on first artificial insemination. Twenty untreated heifers were in estrus in 27 days; 13 (65%) conceived on first artificial insemination.
Keywords: Cattlemen& #x27; s Day; 1974; Report of progress (Kansas State University. Agricultural Experiment Station); 210; Beef; Estrus; Prostaglandin; Syncro-mate B